Combination of stem cell and repetitive transcranial magnetic stimulation in acute ischaemic stroke as a promising treatment: A case report - Danuaji, Rivan; Hambarsari, Yetty; Hamidi, Baarid Luqman; Hutabarat, Ervina Arta Jayanti; Tedjo, Raden Andi Ario; Fairuzya, Azmi Farah; Savitri, Martha Oktavia Dewi (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Stroke is a major contributor to long-term disability and its incidence continues to rise annually. This case report aimed to explore the promising benefits of combining stem cell therapy with repetitive transcranial magnetic stimulation (rTMS) in managing acute ischaemic stroke patients. A 62-year-old male presented with left-sided hemiparesis and hemineglect, as well as a cognitive disturbance in the attention domain. His medical history included uncontrolled hypertension over decades and diabetes mellitus for five years. A non-contrast head computed tomography (CT) scan revealed infarction in the right middle cerebral artery (MCA), with an initial National Institutes of Health Stroke Scale (NIHSS) of 13 upon admission to the Emergency Room. The infection and tumour markers were conducted to confirm no contraindication in this patient receiving stem cell therapy. Following the acute phase, the patient underwent a comprehensive treatment regimen involving both stem cell therapy and serial rTMS. Clinical assessments included NIHSS, Barthel Index, and Fugl-Meyer Assesement to evaluate neurological deficits. Additionally, the Montreal Cognitive Assessment-Indonesian version (MoCA-INA) assessment, electroencephalography examination and motor threshold were conducted. The results of this case report revealed noteworthy improvements in NIHSS, motoric strength, and cognitive function post-treatment. In this case report, improvement in clinical outcomes was obtained in the form of motor strength and higher cortical function. Stem cell therapy combined with rTMS has good potential in treating various neuroregenerative and rehabilitative aspects in ischaemic stroke patients.